Pengaruh Kualitas Produk Dan Brand Awarness Keputusan Pembelian Konsumen Produk Wardah Cosmetic (Studi Kasus Pada Masyarakat Kecamatan Kedungkandang Kota Malang) - Ramadhania, Alisha; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine and analyze the effect of product quality and brand awarness on consumer purchasing decisions for Wardah Cosmetic products in the Kedungkandang District Community, Malang City. The type of research used is explanatory research with a quantitative approach. The research sample was taken by purposive sampling technique with the Malhotra formula used to take the sample, namely 5 × from the total parameters studied so that the sample size was 55 respondents. The data analysis method used in this research is quantitative data analysis using the Validity test and Reliability test, Normality test, Multicollinearity test and Heteroscedasticity test, Multiple Liner Regression Analysis, Hypothesis Test, Test Coefficient of Determination (Adjusted R2). The analysis process uses SPSS. The results of the study state that product quality and brand awareness simultaneously affect purchasing decisions and partially product quality and brand awareness have a positive and significant effect on consumer purchasing decisions. Keywords: Product Quality, Brand Awarness, Purchasing Decisions